2019
DOI: 10.1101/802314
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell RNA sequencing of adultDrosophilaovary identifies transcriptional programs governing oogenesis

Abstract: Oogenesis is a complex developmental process that involves spatiotemporally regulated coordination between the germline and supporting, somatic cell populations. This process has been modelled extensively using the Drosophila ovary. While different ovarian cell types have been identified through traditional means, the large-scale expression profiles underlying each cell type remain unknown. Using single-cell RNA sequencing technology, we have built a transcriptomic dataset for the adult Drosophila ovary and co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 110 publications
(116 reference statements)
0
1
0
Order By: Relevance
“…Thus, we have revealed a new layer of regulation within the signaling network that controls cell behavior in the early FSC lineage. The recently published single cell atlases of the adult Drosophila ovary (Jevitt et al, 2020;Li et al, 2021;Slaidina et al, 2021), revealed a continuum of changes in gene expression that occur during cellular differentiation in the early FSC lineage, and provide the tools for characterizing this signaling network in a cell-type Ben positively regulates JNK signaling in the FSC lineage. JNK signaling downregulates the EGFR signaling reporter pERK and may promote Notch signaling in pFCs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we have revealed a new layer of regulation within the signaling network that controls cell behavior in the early FSC lineage. The recently published single cell atlases of the adult Drosophila ovary (Jevitt et al, 2020;Li et al, 2021;Slaidina et al, 2021), revealed a continuum of changes in gene expression that occur during cellular differentiation in the early FSC lineage, and provide the tools for characterizing this signaling network in a cell-type Ben positively regulates JNK signaling in the FSC lineage. JNK signaling downregulates the EGFR signaling reporter pERK and may promote Notch signaling in pFCs.…”
Section: Discussionmentioning
confidence: 99%